Usina elevatória de traição: um marco para a expansão urbana em São Paulo - Dias, Rafael Ayres de Carvalho (2014)
Placed across the Pinheiros channel, at its midpoint, the Traição Pumping Station is one of the stations that composes the Henry Borden system planned by the Light Co. to generate electricity by altering the natural hydraulic system at the São Paulo plateau, that, in its turn, resulted in the rectification of the river and the possibility of urban use of its floodplain. The station building, showing an architectural treatment that is visual and volumetrically outstanding, suggests the intention to affirm the future of progress and the role that Light played in São Paulo urban sprawl in the mid-twentieth century. Through historical research and the approach of the technical and aesthetic relations of this enterprise, we seek a comprehensive mapping of its purposes and the cultural appreciation in the field of study of architecture and urbanism.